KETIDAKPOPULISAN BAHASA BERITA DALAM PERSPEKTIF BAHASA JURNALISTIK DI MEDIA DARING BATAMNEWS - Lolita, Asri; Lasmaria Sinaga, Juwita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the use of journalistic language in the online media Batamnews. It aims to describe how journalistic language is used in the media. The method used is descriptive qualitative, with the researcher acting as the primary instrument, assisted by a data analysis guideline. The data sources were news articles published in the June 2025 edition of Batamnews. The data examined consisted of words and sentences contained within the articles. Data collection techniques included documentation and hermeneutics. The data analysis technique employed was content analysis, which involved reading, analyzing, describing, and concluding the use of journalistic language in the online media Batamnews. The results showed that 21 news articles in the June 2025 edition did not fully conform to journalistic language standards, particularly regarding unpopularity.